Emotions in the Electronic Educational Space - E. Yu. Novikova (Высшее образование в России)
The study of the role of emotions in education has already established traditions. The relevance of studying emotions in the electronic educational space stems from the expansion of distance education both in Russia and in other countries. System analysis allows us to identify many functions that emotions perform in learning, which include: motivational, meaning-formative, regulatory, communicative, directing, activating, the function of increasing creative potential, integrative, socializing, goal-setting. The retransmission of emotions in the electronic educational space has its own characteristics. Text information plays an important role in e-education. Therefore, the linguistics of emotions, discursive emotions and forms of verbalization of emotiongenic information are of great importance. The concepts of “emotional design” are of methodological importance for the study of emotions in the electronic educational space. The study revealed the different significance of cognitive and transactional emotiongenic factors of electronic space design for students. The most important cognitive emotiongenic factors were named: brightness and accessibility of visual signs, traditions and “customs”, feedback, reliability of the electronic system. The most significant transactional emotiongenic factors were: social communication, visualization, individualization in the design of the site, retransmission of values through the electronic educational space. The significance of emotiongenic factors differs on ZOOM, MOODLE, and LMS. The study of emotions when working in the electronic space allows us to identify areas of University information educational environment development.